Effect-based Hazard Identification of House Dust by In Vitro Assays Detecting Dioxin-like Compounds, Thyroid and Reproductive Toxicants - Suzuki, Go; M. Tue, Nguyen; Takahashi, Shin; Tanabe, Shinsuke; Sakai, Shin-ichi; Takigami, Hidetaka (Current Organic Chemistry, 2014)
Indoor dust is a sink for many kinds of pollutants, including flame retardants (FRs), plasticizers and various degradation products, derived from household products. Recently, we have put particular emphasis on the evaluation of indoor dust as an excellent indicator of important contaminants for chemical risk management throughout the lifecycle of household product. Our research has focused on effect-based approach using in vitro bioassays together with instrumental analyses in an attempt to conduct hazard characterization determining the presence and activity profile of contaminants detected in house dust. This approach will lead to a determination of priority pollutants, their impurities and by-products for further assessment from the list of chemicals manufactured and distributed worldwide. Here, we introduce some background studies and results obtained by using effect-based approach for house dust, revealing importance of dioxin-like compounds, thyroid and reproductive toxicants used and contained in household products. Based on outcomes from previous studies here summarized, it can be suggested that effect-based approach is a useful scheme to determine contaminants and endpoints in indoor dust for priority assessment on in vitro toxicological point of view. Further integration of exposure and effect analysis for indoor dust will lead to appropriate chemical risk management throughout various household products’ lifecycles.
Keywords: CALUX assay